Karakteristik Komposit Bioplastik pada Variasi Rasio Pati Ubi Talas Belitung (Xanthosoma sagittifolium) dan Karagenan - Aritonang, Devi Hagelia; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): September, 2020)
This research was an effort to repair and strengthen the bioplastic pull using Ratio Variations Taro Tuber Starch (Xanthosoma sagittifolium) and Carrageenan. The purposes of the research was to know the effect of the ratio variations of taro tuber starch and carrageenan with glycerol and shakes the bioplastic composites of ratio variation which produces the best characteristics. This research uses factorial random block designs with ratio variations of taro tuber starch and carrageenan with a total 6 grams which consists of 6 levels were 5.5:0.5 ; 5:1 ; 4.5:1.5 ; 4:2 ; 3.5:2.5 and 3:3. The observed variables include mechanical test consisting of tensile strength, elongation at break, modulus young, swelling, biodegradation, and FTIR. The data were analyzed of variant and continued with the HSD Tukey. The result of the research showed that ratio variations of taro starch and carrageenan had significant to elongation at break, very significant effects on tensile strength and modulus young but ratio variations in taro starch and carrageenan non significant to sweeling and biodegradation. The best characteristic with moderate properties standart tensile strength (3.210±0.125) MPa, degradation with ASTM 5336 standart have time 6-7 days, elongation at break (20.7±0.038) %, modulus young (15.912±3.157) MPa, sweeling (43,695 ± 1,151) %, and contain hydrocarbon functional groups -(CH 2 )n, alkenes (CH), amines and amides (CN), alkohols, ethers, carboxylic acids and esters (CO), aldehydes, ketones, esters (C=O ), alkyne (C?C), monomer alkohol (OH), nitro compound (NO 2 ), aromatic ring (C=C), hydrogen bonding carboxylic acid (OH). Keywords: Taro tuber starch, carrageenan, bioplastic composites, tensile strength